Peran Kepala Desa dalam Pengelolaan Dana Desa: Studi Kasus Desa Jepang Pakis Kabupaten Kudus - Wicaksono, Ferio Artahto (STAI Bumi Silampari, 2026)
The village is a community unit authorized to manage governmental affairs and the interests of its citizens, led by a Village Head. One of the main responsibilities of the Village Head is managing village finances, including the village fund (Dana Desa) sourced from the State Budget (APBN). To ensure village funds are used effectively for development, empowerment, and public services, transparent and accountable management is required. This research uses a qualitative approach with an empirical juridical method through interviews, observation, documentation, and a review of laws, regulations, and literature. The purpose of this research is to analyze the implementation of village fund governance by the Village Head and to provide recommendations for improving transparency and accountability. The results show that the management of village funds in Jepang Pakis Village, Jati District, Kudus Regency, is not yet fully in accordance with provisions. A lack of openness is apparent in the planning, implementation, and budget accountability stages, which insufficiently involve the community at large. This leads to information gaps and low public participation. Strengthening governance is necessary through the detailed submission of budget reports, the provision of information via village public media, and the implementation of regular community deliberations (musyawarah) to create transparent, accountable, and participatory village fund management.